2012
DOI: 10.1590/s0100-736x2012000700011
|View full text |Cite
|
Sign up to set email alerts
|

Paracoccidioides brasiliensis infection in dogs from Western Brazilian Amazon

Abstract: The objective of the study was to evaluate Paracoccidioides brasiliensis infection in urban dogs from the municipality of Monte Negro, Rondonia, Western Brazilian Amazon. The serum samples (n=126) were analyzed by indirect ELISA and the immunodiffusion test using P. brasiliensis gp43 and exoantigen as antigens, respectively. A positivity of 54.8% was observed only in the ELISA test and no statistical difference was observed in the seroprevalence in relation to age or sex. This is the ϐirst paracoccidioidomycos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
(37 reference statements)
0
6
0
4
Order By: Relevance
“…Some studies have shown the importance of PCM for the State of Rondônia. Court et al 12 , in a study on dogs as vectors of the fungus in Monte Negro, noted that 54.8% of the dogs that were examined were positive for infection by the fungus, which suggests a high rate of infection in these animals. Forjaz et al…”
Section: Paracoccidioidomycosis (Pcm) Is a Systemic Infection Caused mentioning
confidence: 99%
“…Some studies have shown the importance of PCM for the State of Rondônia. Court et al 12 , in a study on dogs as vectors of the fungus in Monte Negro, noted that 54.8% of the dogs that were examined were positive for infection by the fungus, which suggests a high rate of infection in these animals. Forjaz et al…”
Section: Paracoccidioidomycosis (Pcm) Is a Systemic Infection Caused mentioning
confidence: 99%
“…Sin embargo, otros estudios siguen señalando a la tierra como uno de los hábitats del hongo, argumentan los hechos epidemiológicos el que PCM afecta principalmente a los trabajadores rurales, la alta positividad de paracoccidioidina en los animales que viven en el suelo, en comparación con los animales que habitan los árboles (26) y los estudios epidemiológicos que demuestran que la PCM se produce en varias especies de animales domésticos y salvajes, tales como los perros, específicamente, en Sao Paulo (74,3 a 78,2%), Paraná (14,8 a 89,5%), Mato Grosso do Sul (67,8%), Minas Gerais (53,7%), en Brasil y Argentina (2,2%), también en vacas, caballos, ovejas, monos, cobayas, mapaches, grisones, puercoespines, pollos, armadillos, gatos, perezosos de dos dedos, y una alta incidencia en el armadillo de nueve bandas, Dasypus dasypus que vive en la tierra (27) .…”
Section: Investigaciones Que Contribuyen a La Prevencion Y Control Deunclassified
“…The infection of domestic and wild animals by P. brasiliensis occurs frequently as reported in several epidemiological studies with dogs, horses, cattle, sheep, chickens, goats coati‐mundi, felines, monkeys and armadillos, although natural disease was reported only in two dogs, a cat and a southern two‐toed sloth …”
Section: Introductionmentioning
confidence: 98%
“…7 The serological tests based often on the gp43 antigen are used to diagnose and follow up patients. 8 The infection of domestic and wild animals by P. brasiliensis occurs frequently as reported in several epidemiological studies with dogs, [9][10][11][12] horses, 13 cattle, 14 sheep, 15 chickens, 16 goats 17 coati-mundi, felines, monkeys 18,19 and armadillos, 20,21 although natural disease was reported only in two dogs, 22,23 a cat 24 and a southern two-toed sloth. 25 The first study of experimental PCM in domestic animals was reported by Pereira and Vianna [26] in 1911.…”
Section: Introductionmentioning
confidence: 99%